THE ROLE OF SMALL BUSINESS IN ENSURING FOOD SECURITY IN THE REPUBLIC OF SOUTH OSSETIA - D. Tadtaev; E. Kharebov; A. Gladilin (Вестник Северо-Кавказского федерального университета)
The current realities of the Republic of South Ossetia as a young state are marked by addressing a number of pressing challenges of socio-economic development. In this respect, it is necessary to highlight the problem of food security, which is of a strategic nature and should be given priority by state structures designed to provide it with all-round support. In the Republic of South Ossetia, small enterprises are the main economic entities in the agricultural sector. This article presents an analysis of food production by these enterprises, comparing it with the existing consumption rates, and proposes the main measures to improve food security in RSO.